Diversity and pluralism: A Qur’anic perspective - Khaled, Nashwan Abdo (2020)
The Quranic discourse provides several principles for the concept of pluralism: the origin of diversity and difference - and this origin is a fact of all existence, the origin of freedom and it is the one with which Allah SWT has began to seek his worship through this freedom, and the origin of dialogue to achieve "coexistence" between humans. The Quranic discourse indicates that unity was originally in human beings, and then the difference occurred after it. Allah Almighty says: (And mankind was not but one community [united in religion], but [then] they differed.) (Yunus: 19). Quranic discourse refers to the observance of the principle of pluralism and diversity among human beings, (Say, [O Muhammad], "O mankind, indeed I am the Messenger of Allah to you all, [from Him] to whom belongs the dominion of the heavens and the earth. There is no deity except Him; He gives life and causes death." So believe in Allah and His Messenger, the unlettered prophet, who believes in Allah and His words, and follow him that you may be guided.) (Araf: 158). In many verses, the Quranic discourse refers to the reality of human diversity and pluralism, and that it requires the divine will, and this diversity takes many forms.